Disordered violence : how gender, race and heteronomativity structure terrorism - Gentry, Caron E. (Advances in critical military studies., 2020)
'Disordered Violence' looks at how gender, race and heteronormative expectations of public life shape Western understandings of terrorism as irrational, immoral and illegitimate. Caron Gentry examines the profiles of eight well-known terrorist actors and looks at the gendered, racial, and sexualised assumptions in how their stories are told.